Etika dalam Pelaksanaan Triase Pasien Gawat Darurat - Satti, Yunita Carolina; Ghita, Dwi; Sukrang (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Triage implementation in the Emergency Department (ED) of a hospital is a very important process in emergency patient management, involving technical skills, but also requiring a deep understanding of medical ethics. Methods: This literature review was used with a descriptive approach. The eligibility criteria for the literature were developed based on the Preferred Items for Systematic Reviews and Meta-Analysis (PRISMA) framework, in addition the literature was limited to the range of 2019-2024. Results: Study selection of 439 articles, with 14 articles from PubMed, 200 from Scopus, 200 from Google Scholar, and 25 from the ScienceDirect database. After full-text assessment, 7 articles were included for analysis. Discussion: Triage in emergency patient care is an important process that involves prioritizing patient care based on the severity of their condition. Conclusion: The application of ethics in emergency patient triage requires the integration of the principles of equity, severity-based prioritization, reducing the risk of error, and empathetic communication. Simulation-based training, improving human resources, and educating the public about the importance of ethics-based triage are important steps to ensure justice and patient safety in emergency situations.